Last best hope [compact disc, unabridged] : America in crisis and renewal - Packer, George, 1960- (Macmillan Audio, 2021)
Combining reportage with historical narrative, autobiography, and political analysis, Packer depicts and assesses the four inadequate narratives that dominate American public life: Libertarian America, which imagines a nation of individuals responsible for their own fate, and serves the interests of corporations and the wealthy; Cosmopolitan America, the ideology of Silicon Valley and the professional elite, which celebrates globalization and leaves many American communities behind ; Diverse America, which defines citizens as members of large identity groups that have inflicted or suffered oppression; and White America, a shallow nationalism that fears the contamination of non-whites and treachery of coastal elites, and poses the greatest threat to democracy in our lifetime.